Pengaruh Terapi Okupasi Aktivitas Waktu Luang (Menyapu, Membersihkan Tempat Tidur, Menanam Tanaman dan Menggambar) terhadap Gejala Halusinasi Pendengaran - Rif'ah Fauziah Mustopa; Asih Minarningtyas; Aty Nurillawaty (Jurnal Gema Keperawatan, 2021)
The prevalence of severe mental disorders such as schizophrenia reaches about 400,000 people or as much as 1.7 per 1,000 population. The most common hallucinations are auditory hallucinations, about 70% of patients experience auditory hallucinations, 20% visual hallucinations, and 10% are olfactory, tasting and tactile hallucinations. One of the treatments for hallucinatory patients is occupational therapy. Occupational therapy is a very important way or form of supportive psychotherapy to improve patient recovery. Occupational therapy helps stimulate the patient through activities he enjoys. One type of occupational therapy that is indicated for patients who hallucinate is free time activities such as sweeping, cleaning the bed. The purpose of writing this literature review was to determine the effect of occupational therapy on symptoms in patients with auditory hallucinations based on a literature review search. The design in this scientific paper was a literature review using an electronic database search method and a google schoolar search source. From this writing, found 3 articles on Google Schoolar that discussed the effect of occupational therapy on leisure activities based on classification and outcomes in accordance with the research criteria. The results of the literature review of the three articles show that occupational therapy for leisure activities has an effect on changes in symptoms in patients with auditory hallucinations. Based on these results, occupational activity therapy can be applied to patients with auditory hallucinations to reduce their symptoms.